2022
DOI: 10.13057/biodiv/d230155
|View full text |Cite
|
Sign up to set email alerts
|

Object based classification of benthic habitat using Sentinel 2 imagery by applying with support vector machine and random forest algorithms in shallow waters of Kepulauan Seribu, Indonesia

Abstract: Abstract. Hartoni, Siregar VP, Wouthuyzen S, Agus SB. 2021. Object based classification of benthic habitat using Sentinel 2 imagery by applying with support vector machine and random forest algorithms in shallow waters of Kepulauan Seribu. Biodiversitas 23: 514-520. Benthic habitats have very high complexity and are home to many types of aquatic organisms. Benthic habitats have various functions, including habitat for flora and fauna, sediment traps, nursery areas, and foraging areas for aquatic fauna that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Ao comparar a abordagem pixel a pixel versus orientada a objeto, é perceptível a diferença nos resultados para o SVM (Tabela 5) quando aprimorou todas as métricas de avaliação. Keshtkar et al (2017) e Noi e Kappas (2017) obtiveram resultados semelhantes em que o classificador SVM apresentou as melhores métricas para identificação de diferentes tipos de águas, melhorando a performance, inclusive, quando utilizado método orientado a objeto (Hartoni et al, 2022). Os resultados para KNN e RF foram variados, pois apesar de terem sido mantidos os scores F1 médios, verificou-se que o precision e recall foram mais aleatórios, melhorando para alguns alvos e piorando para Os classificadores pixel a pixel cometeram muitos erros de comissão entre garimpos embarcados e solo, gerando classificações com erros sistêmicos (Figuras 10).…”
Section: Resultsunclassified
“…Ao comparar a abordagem pixel a pixel versus orientada a objeto, é perceptível a diferença nos resultados para o SVM (Tabela 5) quando aprimorou todas as métricas de avaliação. Keshtkar et al (2017) e Noi e Kappas (2017) obtiveram resultados semelhantes em que o classificador SVM apresentou as melhores métricas para identificação de diferentes tipos de águas, melhorando a performance, inclusive, quando utilizado método orientado a objeto (Hartoni et al, 2022). Os resultados para KNN e RF foram variados, pois apesar de terem sido mantidos os scores F1 médios, verificou-se que o precision e recall foram mais aleatórios, melhorando para alguns alvos e piorando para Os classificadores pixel a pixel cometeram muitos erros de comissão entre garimpos embarcados e solo, gerando classificações com erros sistêmicos (Figuras 10).…”
Section: Resultsunclassified
“…Sentinel-2 data have been widely used to map different habitats and several studies have demonstrated their reliability in mapping and monitoring changes in marine biocenoses such as coral (Hedley et al 2012 ), mangrove (Pham et al 2019b , 2020 ) and seagrass beds Topouzelis et al 2016 ; Traganos and Reinartz 2018b ; Ha et al 2020 , 2021 ; Wicaksono et al 2021 ; Nur et al 2021 ; Ivajnšič et al 2022 ; Hartoni et al 2022 ). Many authors have used vegetation indices as the input for RF classification to map plant communities in terrestrial wetlands (Fletcher 2016 ) and coastal wetlands (Zoffoli et al 2020 ; Martínez Prentice et al 2021 ; Benmokhtar et al 2021 ), and compared to many machine learning algorithms and support vector machine techniques, the RF algorithm has produced promising results in terms of classifying seagrass (Zhang et al 2013 ; Traganos and Reinartz 2018b ; Ha et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the extraction of LULC changes and NDVI for vegetation discrimination were obtained by OBIA to specify the existence of illegal MKD farming activities. This is because OBIA entails segmenting images into homogeneous areas and identifying object characteristics using spatial and contextual features (Hartoni et al 2022).…”
Section: Data Acquisition and Methodologymentioning
confidence: 99%